New insights into halophilic prokaryotes isolated from salting–ripening anchovies (Engraulis anchoita) process focused on histamine-degrading strains - Perez, Silvina (2020)
Salted and ripened fish foods are susceptible to cause histamine poisoning. The present study focuses on microbial histamine degradation from high salted fermented fishery products to deepen our understanding about this new and growing field of research. As a result of this first study related to salted-ripened anchovies (Engraulis anchoita), fifty seven moderate and extreme halophilic microbial isolates from salt and salted-ripened anchovy processes were characterized in terms of their phenotype and histamine-degrading capacity. Only 7%-4 isolates-were able to degrade histamine. None of the histamine-degrading isolates presented proteolytic and/or lipolytic activity. One of them designated A18 was chemotactic toward histamine, an interesting property not previously reported for that chemoattractant. However, the S18 and A18 isolates, genotypically identified as Halobacterium sp. and Halomonas sp. respectively, produced indole and/or H₂S, both undesirable characteristics associated to off-flavors occurrence. On the other hand, A28 and S20, identified as Halovibrio sp. and Halobacterium sp. respectively, presented desirable properties, such as cytochrome oxidase and catalase activity, and non-production of H₂S and indole. These strains also showed characteristics previously reported as dominant in the ripened stage. The results are promising, and A28 and S20 may have the desirable features to improve the anchovy salting-ripening process.